1975
DOI: 10.1210/jcem-41-3-511
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cushing's Disease with Reserpine and Pituitary Irradiation†

Abstract: Eighteen patients with Cushing's disease were treated with reserpine and pituitary irradiation. Complete remission was obtained in 9 out of 18 patients after reserpine treatment of 1-2 mg per day for a mean period of 20.4 months, and pituitary irradiation with a mean of 5,865 rads. In another 9 patients, reserpine 0.8-2 mg per day for a mean period of 22.5 months, and pituitary irradiation with a mean of 6,650 rads, were employed. Of these 9 patients, an additional subtotal adrenalectomy was carried out in 6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…The observation that case 1 and 3 remained in remission even after reserpine was discontinued is in agreement with the observation reported by Miura et al(1975), although its explanation remains unclear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observation that case 1 and 3 remained in remission even after reserpine was discontinued is in agreement with the observation reported by Miura et al(1975), although its explanation remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the combination therapy with reserpine irradiation, initially reported by Miura et al(1975), was effective in obtaining complete remission in patients whose surgical treatment was disappointing . In case 1, aminoglutethimide and metyrapone were temporally effective in reducing steroid secretion by their anti-adrenocortical action .…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Of them, follow-up results of 20 patients without further treatment were previously reported (Murayama et al 1992), and the remaining 10 patients (1 man and 9 women, patients 1.10), aged 15 to 59 years (mean±s.D., 32.7+14.2 years) with further treatment are reported here. Eight (1 man and 7 women) of these 10 patients were the same patients described in our previous report (Miura et al 1975),…”
Section: Patients and Treatment Designmentioning
confidence: 85%
“…There were no significant factors predictive of response to our regimen. et al In 1975, we proposed a new treatment regimen consisting of reserpine and pituitary irradiation for Cushing's disease (Miura et al 1975), and recently summarized clinically favorable long term follow-up results in 20 Cushing's disease patients treated with this regimen (Murayama et al 1992). In fact, 11 of the 20 patients (55%) thus treated have been well for a mean of 15.5+8.9 (mean± S.D.)…”
mentioning
confidence: 99%